ANALYSIS OF LEGAL PROTECTION OF BANKING CUSTOMER DATA IN REVIEW OF LAW NUMBER 8 OF 1999 CONCERNING CONSUMER PROTECTION - Polontoh, Herry; Silambi, Sinta Suwarti (MSJ : Majority Science Journal, 2024)
The protection of banking customer data is increasingly important along with the advancement of information technology and the adoption of electronic banking services by the public. Although Law No. 8/1999 on Consumer Protection (UUPK) already exists, it only regulates consumer protection in general and does not specifically regulate the protection of banking customer data. In practice, the implementation of the GCPL is also limited due to the lack of sanctions for customer data breaches. Therefore, this paper examines the international standard personal data regulation that refers to the General Data Protection Regulation (GDPR) to understand more about customer data protection. This paper aims to analyze the legal protection provided to banking customer data in the context of Law No. 8/1999 on Consumer Protection. By examining the provisions of the law, this paper attempts to evaluate the extent to which the existing regulations have been able to effectively protect banking customer data. The analysis shows that although Law No. 9/1999 provides a legal basis for consumer protection in general, the specific protection of banking customer data still needs to be strengthened through more specific regulations and more effective law enforcement mechanisms